From Ideology to Algorithms, The New Face of Fascism: Digital Fascism - Demir, Mustafa (My University, 2025)
Classical fascism is defined as an ideology grounded in authoritarianism and extreme nationalism. Digital fascism, in contrast, is conceptualized as the reproduction and reinforcement of these ideologies through digital platforms such as social media and big data technologies. This study investigates how classical fascism has evolved in the digital era, examining how technological advancements have reshaped authoritarian ideologies. The research employs qualitative methods, including an extensive literature review combined with detailed case analyses. Specifically, the study analyzes platforms such as Facebook, X (formerly Twitter), and the Aadhaar Biometric Identification System, exploring their algorithmic mechanisms and their roles in propagating authoritarian ideologies and enabling constant surveillance. Methodologically, three prominent cases are examined: the Rohingya crisis in Myanmar, surveillance practices in India’s Aadhaar biometric system, and algorithmic manipulation on the X platform during the 2024 U.S. presidential elections. These cases illustrate how digital platforms facilitate hate speech, deepen social polarization, and enable continuous surveillance of individuals through manipulative algorithmic structures. The findings suggest that digital fascism, without requiring a centralized leader or formal organizational structure, has the potential to leverage algorithms to intensify polarization and maintain persistent surveillance, thereby posing significant threats to democratic institutions and individual freedoms. Consequently, the study highlights the necessity of regulating digital platforms in alignment with transparency, ethical principles, and international standards.
Keywords: Social Media; Artificial Intelligence; Fascism; Digital Fascism